Environmental effects of harvesting some Mexican wild edible insects: An overview - Piña-Domínguez, I. A.; Ruiz-May, E.; Hernández-Rodríguez, D.; Zepeda, R. C.; Melgar-Lalanne, G. (Frontiers in Sustainable Food Systems, 2022)
Most traditional edible insects are collected from the forest and agricultural fields, where they are considered pests. However, their importance goes beyond this. They also have an ecological role and potential to be an emerging alternative source of high-quality nutrients that can help satisfy the growing food demand for the human population. Agricultural insect pests are a healthy food source during the harvesting season in many tropical countries. In Mexico, wild insects such as chicatana (queen of flying leaf-cutter ant, Atta mexicana Smith, 1,858; Hymenoptera: Formicidae), chapulín (grasshopper, Pyrgomorphidae), chinicuil (agave red worm, Comadia redtenbacheri Hammerschmidt, 1,848: Lepidoptera, Cossidae), and meocuil (agave white worm, Aegiale hesperiaris Walker 1,856, Lepidoptera, Hesperiidae) are seasonally collected from the agricultural land and forest for food and medicine. Thus, their consumption might be regarded as support for biological plague control. However, in most countries (Mexico included), there is a lack of legislation about edible insects from harvesting to sacrifice and even their main safety aspects. So then, this research aims to provide an updated assessment of the potential use of agricultural pest insects as a sustainable alternative for food, considering current international legislative and ethical concerns about harvesting and consuming wild edible insects, focusing on some of the wild edible pest insects in Mexico.